El papel de la medicina legal en Colombia, aportes y avances de la investigación criminal y en el sistema penal acusatorio (2016)
The criminal investigation in the Colombian criminal system has acquired a number of transformations, in recent years have allowed the criminal investigation to enable judicial authorities to administer justice based on scientific confirmation, such scientific confirmation precedes it after the occurrence of Facts of illicit nature, a series of technical and scientific activities that the organs of the State with functions of Judicial Police perform in order to collect the physical evidence and the material elements of evidence that allow to know and understand a crime; This is how criminal investigation becomes the backbone of the criminal system in Colombia, since each of the stages that make up the same is of paramount importance for the proper conduct of the investigation; Even the slightest error in judicial proceedings (collection, chain of custody, opinions and others) may affect the verification of the occurrence of the act, the establishment of perpetrators and participants in the punishable conduct, the determining reasons that influenced the violation Of the criminal law, the framing of the type and circumstances of time, mode and place in which the conduct was carried out